Awake prone positioning and ventilation distribution as assessed by electric impedance tomography in patients with non-COVID-19 acute hypoxemic respiratory failure: A prospective physiology study - Jingjing Wang; Changxing Chen; Zhanqi Zhao; Puyu Deng; Chenchen Zhang; Yu Zhang; Hui Lv; Daonan Chen; Hui Xie; Ruilan Wang (Journal of Intensive Medicine)
Background: Awake prone positioning (APP) can reportedly reduce the need for intubation and help improve prognosis of patients with acute hypoxemic respiratory failure (AHRF) infected with COVID-19. However, its physiological mechanism remains unclear. In this study, we evaluated the effect of APP on lung ventilation in patients with moderate-to-severe AHRF to better understand the effects on ventilation distribution and to prevent intubation in non-intubated patients. Methods: The prospective study was performed in the Department of Critical Care Medicine at Shanghai General Hospital, China, from January 2021 to November 2022. The study included patients with AHRF (partial pressure of oxygen [PaO2]/inspired oxygen concentration [FiO2] <200 mmHg or oxygen saturation [SpO2]/FiO2 <235) treated with high-flow nasal oxygen. Electrical impedance tomography (EIT) measurements including center of ventilation (COV), global inhomogeneity (GI) index, and regional ventilation delay (RVD) index were performed in the supine position (T0), 30 min after the start of APP (T1), and 30 min returning to supine position after the APP (T2). Clinical parameters like SpO2, respiratory rate (RR), FiO2, heart rate (HR), and ROX (the ratio of SpO2 as measured by pulse oximetry/FiO2 to RR) were also recorded simultaneously at T0, T1, and T2. To evaluate the effect of the time points on the variables, Mauchly's test was performed for sphericity and repeated measures analysis of variance was applied with Bonferroni's post hoc multiple comparisons. Results: Ten patients were enrolled. The PaO2/FiO2 ratio was (111.4±33.4) mmHg at the time of recruitment. ROX showed a significant increase after initiation of APP {median (interquartile range [IQR]): T0: 7.5 (6.0–10.1) vs. T1: 7.6 (6.4–9.3) vs. T2: 8.3 (7.2–11.0), P=0.043}. RR (P=0.409), HR (P=0.417), and SpO2/FiO2 (P=0.262) did not change significantly during prone positioning (PP). The COV moved from the ventral area to the dorsal area (T0: 48.8%±6.2% vs. T1: 54.8%±6.8% vs. T2: 50.3%±6.1%, P=0.030) after APP. The GI decreased significantly after APP (T0: median=42.7 %, [IQR: 38.3%–47.5%] vs. T1: median=38.2%, [IQR: 34.6%–50.7%] vs. T2: median=37.4%, [IQR: 34.2%–41.4%], P=0.049). RVD (P=0.794) did not change after APP. Conclusions: APP can improve ventilation distribution and homogeneity of lung ventilation as assessed by EIT in non-intubated patients with AHRF.Trail Registration Chinese Clinical Trial Registry Identifier: ChiCTR2000035895.